Advancing commission scholarship by inferring leadership legacy motivations from commission reports: The case of Sir Michael Lyons. (April 2018) - Wallis, Joe; Brodtkorb, Tor; Dollery, Brian
This article contributes to commission scholarship by exploring how and why chairs use their reports to shape their leadership legacies. It distinguishes two types of legacy – fiduciary and expressive – that chairs shape through their reports. The expressive legacy of the chair can be shaped through judgements about the scope of stakeholder engagement and agenda adjustment that generate four types of leadership identity: conservator, consolidator, advocate and catalyst. We explore the particular ways in which the chair of the Lyons Inquiry into Local Government in the UK used his three reports to shape his legacy. Through his distinctive integration of historical and contemporary perspectives into a leading vision for local government, he expressed a consolidator identity with his short-term recommendations and a catalytic identity with his far-reaching envisioning of the institutional space within which a greater place-shaping role for local government could be established.